Drill String Failure Analysis and Erosion Wear Study at Key Point for Gas Drilling. Issue 3 (June 2014) - Liu, Shaohu; Zheng, Hualin; Zhu, Xiaohua
Erosion wear at the key point of a drill string is very severe in gas drilling. The investigation shows that failure of drill string is very serious in gas drilling. The probability of failure of the drill pipe and the drill collar is the highest in all the drill string, and the near placement of pin and box is often damaged. According to the investigation of drill string failure and erosion theory, the erosion model of drill string is established. The erosion rate at the key point of a drill string is solved using the Grant and Tabakoff formula. Different factors, such as gas injection volume, rate of penetration (ROP), cuttings' diameter, cuttings' shape factor, cuttings' number, and temperature of the annulus, are considered. The result shows that the erosion rate at the key point is more severe than that of other locations on the drill pipe. Because of higher peak stress for a drill string with eroded wear, there is a more serious effect on the residual strength of a drill string with eroded wear. Crack forms easily, due to severe erosive wear and deeper pits. Also, fracture failure of a drill string is caused by larger axial load and torque. In this paper, analysis of such influencing parameters as gas injection volume, ROP, cuttings' particle size, cuttings' shape factor, cuttings number and temperature of the annulus is conducted, among which gas injection volume, ROP and cuttings number are proven as the main controlling factors that affect the erosion wear at the key point of a drill pipe.